Tourists’ Willingness to Use AI-Enabled Chatbots : Extending the Technology Acceptance Model - Sobhan, Sanjana; Oishi, Oaisharia Vocto; Hossain, Md. Manower; Sultana, Mousumi; Hossain, Md. Julhaz (Indian Journal of Marketing, 2026)
Purpose : Grounded on the technology acceptance model (TAM), this study aimed to investigate the determinants that affected tourists’ willingness to use artificial intelligence (AI)-enabled chatbots for tourism and hospitality services in Bangladesh. Methodology : A quantitative online survey was employed to collect data using a purposive sampling technique from 470 Bangladeshi tourists who had experience with AI-based chatbot services. The partial least squares-structural equation modeling (PLS-SEM) was employed to estimate the obtained data and test the hypothesized relationships. Findings : The findings revealed that chatbots’ perceived intelligence, ease of use, and usefulness significantly impacted tourists’ attitudes toward chatbot use ; whereas, perceived interactivity did not have a substantial effect. Furthermore, perceived ease of use significantly influenced perceived usefulness, and tourists’ attitudes had a noteworthy effect on their willingness to use chatbots. In addition, attitude toward chatbot use successfully mediated the relationship between perceived intelligence and willingness to use chatbots and perceived ease of use and willingness to use chatbots; however, it was unable to mediate the relationship between perceived interactivity and willingness to use chatbots. Practical Implications : This study left noteworthy implications for adopting AI-based chatbots within the tourism and hospitality domain, benefiting policymakers, scholars, tourism enterprises, tourists, and other stakeholders. Originality : The novelty of the study lies in the interplay of proposed relationships among key constructs, employing the TAM, to examine tourists’ willingness to use AI-enabled chatbots in a new direction.